Analisis Yuridis Sistem Multi Partai Politik Sebagai Upaya Peningkatan Kualitas Demokrasi Di Indonesia - Sabili, Khoiril; Yazwardi, Yazwardi; Afriansyah, Syafran; Rochmiatun, Siti; Utama, Cholidah (Lex Librum : Jurnal Ilmu Hukum, 2025)
Indonesia as a country adopting a presidential system of government and embracing a multi-party system.According to the 2013 Democracy Index, by 2023, the quality of democracy in Indonesia is still in the category of flawed democracies and not fully democratic. (post democracy). How did he analyze the multi-party political system in an effort to improve the quality of democracy in Indonesia? How is it conceptualized as a state of natural law in Indonesia? Understanding the legal system of the multi-party political system as an attempt to improve the quality of democracy in Indonesia and the conceptualization of the opposition party in the multi -party system on the rule of law in Indonesia. The methods used in research are the historical approach, the comparative approach and the conceptual approach. (conceptual approach). Political scenarios attempt to introduce electoral thresholds, parliamentary thresolds and presidential thresholes in the electoral process, but less effective. Strategic steps to transform the party system into a limited multi-party system and elections into an open semi-district system to enhance the quality of democracy in Indonesia. Regulation of the rules of existence of opposition parties is essential in a democratic system, as an advocate for improving the quality of democracy. The opposition party serves as a supervisor of government policy, provides constructive criticism, and offers policy alternatives.